Proceedings of the 45th Annual Design Automation Conference 2008
DOI: 10.1145/1391469.1391712
|View full text |Cite
|
Sign up to set email alerts
|

Efficient system design space exploration using machine learning techniques

Abstract: Computer manufacturers spend a huge amount of time, resources, and money in designing new systems and newer configurations, and their ability to reduce costs, charge competitive prices and gain market share depends on how good these systems perform. In this work, we develop predictive models for estimating the performance of systems by using performance numbers from only a small fraction of the overall design space. Specifically, we first develop three models, two based on artificial neural networks and anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…Learning-based methods were proposed to guide the DSE process by predicting solution qualities before running actual simulation/synthesis [1,8,10,11,17]. Compared with local-search techniques, learning-based methods can yield better solution quality as well as require shorter simulation/synthesis runtime.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning-based methods were proposed to guide the DSE process by predicting solution qualities before running actual simulation/synthesis [1,8,10,11,17]. Compared with local-search techniques, learning-based methods can yield better solution quality as well as require shorter simulation/synthesis runtime.…”
Section: Related Workmentioning
confidence: 99%
“…Within this framework, two very recent papers [8,17] independently reported that Gaussian Process [17], a.k.a. Kriging [8], was the most promising learning model, superior to Artificial Neural Network [10,11] and other simple models. These results were obtained from DSE with processor simulators [8] or IP generators [17].…”
Section: Related Workmentioning
confidence: 99%
“…The link between the parameters of ANNs and understandable facts is typically hard to establish, hence they are not useful as interface for engineers to specify facts. Predictive models in a more general matter are also used by Ozisikyilmaz et al [20] to accelerate DSEs.…”
Section: Related Workmentioning
confidence: 99%
“…However, since the required processing power exceeds that available in the field, the generation and update of rules occurs offline. Other projects exist that use run time learning techniques such as supervised learning which require additional training information [10], or in which learning is used solely to optimize the system during design time [11]. The goal of ASoC is to provide both adaptivity and learning at run time, and to do so within the constraints of a typical system on chip design.…”
Section: Prior Artmentioning
confidence: 99%